2018
DOI: 10.1002/jor.24044
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of biomarkers to identify peri‐implant osteolysis before radiographic diagnosis

Abstract: Peri-implant osteolysis is commonly diagnosed after substantial bone loss has occurred, making revision surgery more challenging. The goal of the current study was to identify urinary biomarkers that differentiate total hip replacement patients who eventually develop osteolysis from patients who do not. We used a repository of 24-h urine samples collected prior to surgery and annually thereafter in 26 patients, 16 who developed osteolysis, and 10 who did not. We examined the markers at radiographic diagnosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…β-CTX is a piece of collagen released into the blood after degradation in the process of bone remodeling. The increase of β-CTX content reflects the degree of bone absorption and the increase of bone loss, leading to the occurrence of osteoporosis and deformable osteopathy, [ 31 ] such as GSD. β-CTX is a commonly used biomarker of osteoclastic bone resorption for the prediction of bone mass loss.…”
Section: Discussionmentioning
confidence: 99%
“…β-CTX is a piece of collagen released into the blood after degradation in the process of bone remodeling. The increase of β-CTX content reflects the degree of bone absorption and the increase of bone loss, leading to the occurrence of osteoporosis and deformable osteopathy, [ 31 ] such as GSD. β-CTX is a commonly used biomarker of osteoclastic bone resorption for the prediction of bone mass loss.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examinations reveal that Ti wear debris with a diversity of sizes and crystal structures accumulate in the synovia-like peri-implant membrane, bone marrow as well as periimplant regions that are affected by brotic and in ammatory changes [6]. Due to their high persistency (low solubility), the interaction of wear debris with cells and tissues induce a complex immune response that can lead to periprosthetic osteolysis (degeneration of bone causing aseptic loosening) and implant failure with a consequent need of a revision surgery [3][4][5][7][8][9][10]. Besides the severe consequences for the patients' health conditions (e.g., higher rates of mortality, hospital readmission, dislocation, and infection), revision surgeries pose a high nancial burden on healthcare systems (longer surgery time, expensive prostheses, longer hospitalization periods, and higher rates of health complications) [10][11].…”
Section: Discussionmentioning
confidence: 99%
“…The main biological mechanisms underlying the response to Ti wear debris are innate immune response where the phagocytosis of wear particles induces macrophages activation [12]. The reactivity of macrophage results in a pro-in ammatory milieu (up-regulation of pro-in ammatory cytokines, mainly IL-1b, IL-6, and TNF-alfa) in the proximity of bone that perturb its homeostasis (reduced osteoblastogenesis and increased osteoclastogenesis) leading to periprosthetic bone osteolysis [5,[7][8][9][10]12]. Although chronic in ammatory reaction is mostly driven by macrophages, osteolysis is also indirectly caused by the contribution of other cell types such as osteoblasts, dendritic cells, osteoclasts, and synovial broblasts.…”
Section: Discussionmentioning
confidence: 99%
“…As an individual biomarker, DPD demonstrated the highest ability to predict osteolysis, with an area under the curve (AUC) in Receiver Operating Characteristic (ROC) analyses of 0.844 at 6 years prior to diagnosis. A panel of α-CTX and IL-6 was able to identify at-risk patients with an AUC of 0.941 or greater at all post-operative time points and an AUC of 1.000 pre-operatively, suggesting the role for such biomarkers in the detection of pre-clinical PPOL [ 88 ]. In the only other series in the literature, Li et al found that biomarker levels, specifically osteocalcin and cross-linked carboxyterminal telopeptide of type I collagen (ICTP), were elevated before implant migration as assessed by radiosteriometric analysis (RSA) in their cohort of 40 TKAs [ 89 ].…”
Section: Biomarkersmentioning
confidence: 99%